Incidence and relevance of QTc-interval prolongation caused by tyrosine kinase inhibitors - Kloth, J S L (Br J Cancer, 2015)
BACKGROUND: Tyrosine kinase inhibitors (TKIs) are associated with prolongation of the QTc interval on the electrocardiogram (ECG). The QTc-interval prolongation increases the risk of life-threatening arrhythmias. However, studies evaluating the effects of TKIs on QTc intervals are limited and only consist of small patient numbers. METHODS: In this multicentre trial in four centres in the Netherlands and Italy we screened all patients who were treated with any TKI. To evaluate the effects of TKIs on the QTc interval, we investigated ECGs before and during treatment with erlotinib, gefitinib, imatinib, lapatinib, pazopanib, sorafenib, sunitinib, or vemurafenib. RESULTS: A total of 363 patients were eligible for the analyses. At baseline measurement, QTc intervals were significantly longer in females than in males (QTc(females)=404 ms vs QTc(males)=399 ms, P=0.027). A statistically significant increase was observed for the individual TKIs sunitinib, vemurafenib, sorafenib, imatinib, and erlotinib, after the start of treatment (median ΔQTc ranging from +7 to +24 ms, P<0.004). The CTCAE grade for QTc intervals significantly increased after start of treatment (P=0.0003). Especially patients who are treated with vemurafenib are at increased risk of developing a QTc of ⩾470 ms, a threshold associated with an increased risk for arrhythmias. CONCLUSIONS: These observations show that most TKIs significantly increase the QTc interval. Particularly in vemurafenib-treated patients, the incidence of patients at risk for arrhythmias is increased. Therefore, especially in case of combined risk factors, ECG monitoring in patients treated with TKIs is strongly recommended.